Percepción de riesgo, creencias y normas subjetivas de la conducta proambiental en pobladores del sector ladrillero del distrito de San Jerónimo, Cusco, 2019 - Cornejo, Ana (2019)
Abstract  The research aims to study the relationship between risk perception, beliefs and pro-environmental subjective norms in the brick sectors of the district of San Jerónimo, Cusco. Three previously validated instruments were applied to 205 inhabitants of the brickyards. A quantitative, descriptive-correlational and cross-sectional methodology was used. The results showed the relationship between risk perception and pro-environmental beliefs, indicating a direct positive correlation of r = .43 and a value of p <0.000; the relationship between risk perception and subjective norms indicate a weak positive correlation (r = .33) and a p value <0.001 and the relationship between pro-environmental beliefs and subjective norms indicate a significant positive correlation r = .44 and a p value <0.001. The descriptive result shows a high level of perception of risk (63.4%), pro-environmental beliefs (66.3%); however, the subjective standards (56.1%) have a medium level. Conclusion: the inhabitants of the brickyards have pro-environmental perceptions, beliefs and subjective norms with the intention of reducing behaviors that deteriorate the environment, but this result is not reflected in their behavior.Key Words: Risk perception, pro-environmental beliefs, subjective norms, pro-environmental behavior.